Strategic green infrastructure planning in Germany and the UK: a transnational evaluation of the evolution of urban greening policy and practice. Issue 4 (2nd October 2017) - Mell, Ian; Allin, Simone; Reimer, Mario; Wilker, Jost
ABSTRACT: The evolution of Green Infrastructure (GI) planning has varied dramatically between nations. Although a grounded set of principles are recognized globally, there is increasing variance in how these are implemented at a national and sub-national level. To investigate this the following paper presents an evaluation of how green infrastructure has been planned for in England and Germany illustrating how national policy structures facilitate variance in application. Adopting an evaluative framework linked to the identification of GI, its development and monitoring/feedback the paper questions the impacts on delivery of intersecting factors including terminology, spatial distribution and functionality on effective GI investment. This process reviews how changing policy structures have influenced the framing of green infrastructure policy, and subsequent impact this has on the delivery of green infrastructure projects.